PSYCHOLOGICAL FEATURES OF INTERPERSONAL COMMUNICATION OF PRECINCT OFFICERS OF THE NATIONAL POLICE OF UKRAINE - Shvets, Dmytro; Barko, Vadym; Boiko-Buzyl, Yuliia (PSYCHOLOGICAL JOURNAL, 2021)
The article highlights the results of the study of psychological features of interpersonal interaction of district officers of the National Police of Ukraine. A district police officer, like every police officer, in the process of professional activity performs important law enforcement functions to ensure security, respect for rights and freedoms, on the basis of partnership and police care, so close contact with citizens and colleagues, so his communicative potential depends on the success of official tasks. The ability to communicate with people, establish psychological contact, overcome barriers to communication, listen, listen and hear, answer questions, influence, provide and obtain the necessary information, etc., determine not only the quality of work of a police officer in general, but also efficiency activities of the National Police of Ukraine in general. The presented study of interpersonal communication of police officers is based on the use of two recognized psychodiagnostic methods, namely the interrogation questionnaire for interpersonal interaction T. Leary and the abbreviated version of the questionnaire of the Big Five in the adaptation of O. John, L. Naumann, S. Soto. In general, the selected questionnaires allowed to determine the professional features of communication of district police officers in the vectors of extroversion and introversion, friendliness and aggression, dominance and dependence. The profile of a district police officer has been found to combine wall and hyposthenic characteristics, allowing them to combine stern, masculine traits and patterns of behavior in interpersonal relationships with milder, emotionally benevolent manifestations. Personal characteristics such as honesty, extroversion, moderate flexibility, openness to new experiences, low levels of neuroticism indicate that district police officers tend to have a mixed type of response in the process of interpersonal interaction. It has been proven that the use of questionnaires provides an objective and comprehensive description of the style of interpersonal behavior of police officers, which will improve the quality of professional selection of police officers, increase the efficiency of teamwork and increase public confidence in the police.